"Crimean Syndrome": Mechanisms of Authoritarian Mobilization. Issue 4 (2nd November 2021) - Rogov, Kirill
Abstract : The rapid shift in mass public opinion among Russians after the annexation of Crimea is usually attributed to the success of official state propaganda. This article asks how this success was achieved, given that the popularity of Putin's regime had been falling for several years while the opposition had been gaining strength. The war enabled the regime to return poorly informed citizens to political life while serving as an excuse to repress regime opponents.